The Influence of TikTok, Brand Ambassador, and Brand Awareness on Shopee’s Purchase Interest - Nurjannah, Alfida; Surianto, Moh. Agung (International Journal Labs, 2022)
Background: The growing use of social media is proof that social media is very popular with the public today because it is easy to use and use. Indonesia itself internet media users show that very many Indonesian people as internet users mauoun social media in it. Aim: This study aims to test the influence between independent variables with dependent variables. Method: This study was conducted in the case study of the University of Muhammadiyah Gresik management students class 2018-2021 as a population in this study with the number of samples used, namely as many as 75 respondents and purposive sampling sample withdrawal techniques. Analytical techniques in hypothesis testing using statistical analysis tools such as Statistical Package for the Social Science (SPSS). Findings: The results of the study showed that Tiktok Social Media (X1), Brand Ambassador (X2), Brand Awareness (X3) each have a positive and significant impact on Purchase Intention (Y).